ANALISIS KOMPREHENSIF PERAN STRATEGIS KEPALA SEKOLAH DALAM MEWUJUDKAN SEKOLAH BERKUALITAS DI INDONESIA: - Laura Novita (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the strategic role of school principals as educational leaders in realizing quality schools. The significance of this study lies in the importance of leadership in improving educational outcomes and managing school effectiveness. This research employs a qualitative approach using library research, focusing on the analysis of relevant theories and previous studies from scientific books and journals. The data were collected through documentation techniques and analyzed using content analysis, including data reduction, data presentation, and conclusion drawing. The results show that the principal plays a crucial role in determining school quality through effective leadership, comprehensive task implementation, and strategic decision-making. In addition, the findings indicate that transformational leadership is an effective strategy in enhancing teacher performance, fostering innovation, and creating a positive school culture. The study also reveals that the complexity of principals’ responsibilities requires strong managerial and leadership competencies. In conclusion, the success of improving educational quality is highly dependent on the principal’s leadership capacity. Therefore, continuous professional development and strengthening leadership competencies are essential to support principals in facing educational challenges and achieving sustainable school improvement. ABSTRAK Penelitian ini bertujuan untuk menganalisis peran strategis kepala sekolah sebagai pemimpin pendidikan dalam mewujudkan sekolah yang berkualitas. Pentingnya penelitian ini terletak pada peran kepemimpinan dalam meningkatkan mutu pendidikan dan efektivitas pengelolaan sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi pustaka yang berfokus pada analisis teori dan hasil penelitian terdahulu dari buku dan ilmiah. Teknik pengumpulan data dilakukan melalui studi dokumentasi, sedangkan analisis data menggunakan analisis isi yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kepala sekolah memiliki peran penting dalam menentukan kualitas sekolah melalui kepemimpinan yang efektif, pelaksanaan tugas yang komprehensif, serta pengambilan keputusan yang strategis. Selain itu, kepemimpinan transformasional terbukti menjadi strategi yang efektif dalam meningkatkan kinerja guru, mendorong inovasi, serta menciptakan budaya sekolah yang positif. Penelitian ini juga menunjukkan bahwa kompleksitas tugas kepala sekolah menuntut kompetensi manajerial dan kepemimpinan yang kuat. Dengan demikian, peningkatan mutu pendidikan sangat bergantung pada kualitas kepemimpinan kepala sekolah sehingga diperlukan pengembangan profesional secara berkelanjutan.